Assessment of Sedimentation Problem in Kenyir Hydropower Reservoir - Chow M.F.; Subbramaniam P.; Sidek L.M. (IOP Publishing Ltd, 2023)
Catchments; Digital storage; Hydroelectric power; Hydroelectric power plants; Land use; Sedimentation; Capacity data; Comprehensive monitoring; Heavy storms; Hydropower reservoirs; Land-use change; Reservoir catchments; Sediment loads; Soil erosion; Reservoirs (water)